Application of Artificial Intelligence (AI) in Ship Route Management to Reduce Fuel Consumption - Dewi, Ratna Kurnia (UNIVERSITAS PAKUAN, 2025)
The application of artificial intelligence (AI) in ship route management is increasingly gaining attention in the shipping industry as a solution to improve operational efficiency and reduce fuel consumption. The maritime industry faces major challenges related to high operational costs and significant carbon emissions. Therefore, this study aims to analyze the effectiveness of AI in optimizing ship navigation to reduce fuel consumption. This study uses a quantitative method with an experimental approach and case studies, where data is collected through direct observation, interviews with ship operational managers, and analysis of documents related to fuel consumption before and after the application of AI. The results show that ships using AI experience a reduction in fuel consumption of 15-25% compared to conventional methods. Multiple linear regression analysis reveals that ship speed, ocean currents, and the selected route contribute significantly to fuel efficiency. Although the application of AI provides economic and environmental benefits, there are several challenges, such as high initial investment costs, limited digital infrastructure in some waters, and resistance of ship crews to new technologies. Therefore, this study recommends improving digital infrastructure, collaboration between shipping companies and governments, and training for ship crews to increase the adoption of AI in the maritime sector. With the right strategy, AI has the potential to be a key solution in creating a more efficient and sustainable shipping industry.